THE USE OF THE QUANTUM TEACHING MODEL ON STUDENT LEARNING OUTCOMES IN MATHEMATICS CLASS II SDN 158/VIII RIMBO MULYO - Roviani, Suzi (The Future of Education Journal, 2023)
The use of learning models that are not appropriate during the learning process causes students to get bored and bored so that students are less active when learning activities take place so that students do not understand the material because there is too much material and most of them take notes, and the impact on learning outcomes is very low. The Quantum Teaching Model This researcher aims to improve learning outcomes with the Quantum Teaching model for Class II SDN 158/VIII Rimbo Mulyo. This type of research is class action research (Classroom Action Research). This study aims to determine learning in mathematics subject matter of time measurement. The research subjects were class II students at SDN 158/VIII Rimbo Mulyo. Methods of data collection is done through documentation, observation and tests. The work procedure in this study is an activity cycle consisting of two cycles. Where each - each cycle through the stages - the stages that must be taken namely planning, implementation of action, observation, reflection. The completeness criterion is 70 where the learning outcomes of students are said to be complete if they meet these criteria. The results of the research show that the Quantum Teaching model can improve student learning outcomes. This can be seen from the average pre-cycle score of 61.21, the first cycle is 67.88 and the second cycle is 73.03. While the percentage in the pre-cycle was 42.42%, the first cycle was 60.61% and the second cycle was 81.81%. This means that research at this stage is sufficient because students have met the specified KKM, namely 70.